Booker T. Washington in American Memory - Hamilton, Kenneth Marvin, 1947- (Book collections on Project MUSE., 2017)
"This project examines the response to Booker T. Washington's death, analyzing the many ways in which both black and white Americans involved in the Yankee Protestant Ethic Movement honored or memorialized the great visionary. The northern-based Movement originally saw southerners as a people who embraced a profane ethic, one that undermined the glory of the nation. In order to shift southerners away from their lazy, inefficient, and uneducated ways, the Movement engaged them in a culture war that employed multiple educational and evangelical agencies. When white southerners resisted such interference, the Movement began concentrating more exclusively on black southerners. Washington became an advocate for the Movement, and in turn the Movement became a cornerstone of Washington's ideology. After Washington's death, leading supporters of the Movement wanted to perpetuate his vision. They used obituaries, burial rites, memorials, and eulogies as weapons of choice in their efforts to continue a culture war between a supposedly democratic North and a seemingly aristocratic South. Hamilton reexamines Washington's influences, thereby producing a new understanding of his life. Integrating an analysis of letters of solace, obituaries, and other archival documents, Hamilton examines the ways that the memory of Washington and his works were cultivated and utilized by his contemporaries to promote racial consciousness. By closely working with the documents that reflect the memory and admiration of Washington at the time of his death, Hamilton is also able to show how recollections of Washington have shifted or become obscured by more recent historical assumptions or interpretations."--Provided by publisher.